Early adolescent Internet game addiction in context: How parents, school, and peers impact youth. (September 2015) - Zhu, Jianjun; Zhang, Wei; Yu, Chengfu; Bao, Zhenzhou
Highlights: A direct pathway from PAR to IGA was not evident in the final model. A fully indirect effect of PAR on IGA highlighted the protective role of SC. DPA fully mediated the link between PAR and IGA. A sequential mediation path appeared in the final model. The impacts of factors in various contexts on IGA were intertwined with each other. Abstract: The aim of this study was to identify the underlying mediating mechanisms between the parent–adolescent relationship and Internet game addiction (IGA). A sample of 833 adolescents initially in the 7th grade completed anonymous questionnaires regarding the parent–adolescent relationship, school connectedness, deviant peer affiliation, and IGA during a one year period. Structural equation models showed that both school connectedness and deviant peer affiliation fully mediated the association between the parent–adolescent relationship and adolescent IGA. School connectedness also significantly predicted deviant peer affiliation, forming a sequential mediation model. In general, the results indicated that a low quality parent–adolescent relationship predicted IGA by way of diminishing school connectedness and enhancing affiliations with deviant peers. The non-significant pathway from parent–adolescent relationship to adolescent IGA supports the idea that a distal parent–adolescent relationship still retains a substantial influence on the development of adolescents' IGA, but through the more important proximal variables of school connectedness and deviant peer affiliation. Identifying the processes by which the parent–adolescent relationship is associated with adolescents' IGA has important implications for developing an integrative framework of theory and prevention.